A retrospective analysis of ectopic pregnancy at a tertiary care centre: one year study - Bhuria, Vandana; Nanda, Smiti; Chauhan, Meenakshi; Malhotra, Vani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is an important cause of maternal morbidity and mortality especially in developing countries where the majority of patients present late with rupture and hemodynamic compromise. The aim of this study was to determine the risk factors, clinical profile of the patients and management options for ruptured ectopic pregnancies. Methods: We conducted a retrospective study about ectopic pregnancy at obstetrics and gynaecology department over a period of one year, from 01 January 2015 to 31 December 2015. Information on the biosocial data, clinical symptoms and signs, risk factors for the disease, site of ectopic pregnancy and treatment options, quantity of hemoperitoneum and need for blood transfusion was extracted. The data was analyzed and presented in frequency tables and charts. Results: Frequency of ectopic pregnancy was 1.6% of total 10235 deliveries. 131 (89.1%) cases were of ruptured ectopic pregnancy. 147 patients underwent laparotomy while 22 patients were managed conservatively. All patients were symptomatic at presentation. Majority (86, 50.8%) of the patients were in the age group of 20-24 years. 33 (19.5%) patients were nulliparous. Risk factors were found in 86 (50.8%) patients. Majority (38, 44.1%) had history of previous tubal surgery (tubal sterilization and/or recanalisation) as risk factor. The highest number of ruptured ectopic occurred between 7-12 weeks of gestation. Most common surgical procedure employed was salpingectomy in 140 (95.2%) patients. There was no maternal mortality due to ectopic pregnancy. Conclusions: Ectopic pregnancy is still a major life threatening emergency condition which if treated early has good prognosis. Most cases present late making tubal conservation inapplicable. Efforts should be made towards woman education, improved hospital accessibility and better diagnostic skills.